2021
DOI: 10.1186/s12879-021-06813-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between tocilizumab and emerging multidrug-resistant organisms in critically ill patients with COVID-19: A multicenter, retrospective cohort study

Abstract: Background Tocilizumab is an IgG1 class recombinant humanized monoclonal antibody that directly inhibits the IL-6 receptor. Several randomized clinical trials have evaluated its safety and efficacy in patients with coronavirus disease 2019 (COVID-19), and these studies demonstrate conflicting results. Our study aimed to determine the association between tocilizumab treatment and microbial isolation and emergence of multidrug-resistant bacteria in critically ill patients with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This study was carried out under the auspices of the Saudi Critical Care Pharmacy Research (SCAPE) platform, which also conducted other investigations to evaluate the safety and effectiveness of various therapies in critically ill patients ( SCAPE, n.d. ). The methodology of this multicenter cohort study is comparable to other studies executed by the SCAPE platform and previously reported ( Al Harbi et al, 2022 , Al Sulaiman et al, 2022b , Al Sulaiman et al, 2022a , Al Sulaiman et al, 2021a , Al Sulaiman et al, 2021b , Aljuhani et al, 2021 ). The supplemental material contains additional details on the study's design.…”
Section: Methodssupporting
confidence: 59%
“…This study was carried out under the auspices of the Saudi Critical Care Pharmacy Research (SCAPE) platform, which also conducted other investigations to evaluate the safety and effectiveness of various therapies in critically ill patients ( SCAPE, n.d. ). The methodology of this multicenter cohort study is comparable to other studies executed by the SCAPE platform and previously reported ( Al Harbi et al, 2022 , Al Sulaiman et al, 2022b , Al Sulaiman et al, 2022a , Al Sulaiman et al, 2021a , Al Sulaiman et al, 2021b , Aljuhani et al, 2021 ). The supplemental material contains additional details on the study's design.…”
Section: Methodssupporting
confidence: 59%
“…We administered tocilizumab in one case only. Data from Aljuhani et al [24] revealed the lack of association between such treatment and the incidence of MDR.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed no difference in the length of stay; similarly, a systematic review and metaanalysis by Rezaei et al showed no statistically significant difference in hospital length of stay. 17 We believe our study is one of the first studies that suggest a potential role of TCZ in preventing multiorgan dysfunction in critically ill patients with COVID-19 if further confirmed in large RCTs. The aforementioned trials studied organ dysfunction in terms of respiratory and cardiovascular organ support free day in the REMAB-CAP and receiving mechanical ventilation or hemofiltration in the RECOVERY trial while our study measured the MOD score which accounts for the severity of MOD in six organ systems including respiratory, cardiovascular, renal, hematological, hepatic failure, and central nervous system.…”
Section: Discussionmentioning
confidence: 54%
“…Our results showed no difference in the length of stay; similarly, a systematic review and meta-analysis by Rezaei et al showed no statistically significant difference in hospital length of stay. 17 …”
Section: Discussionmentioning
confidence: 99%